Jam’ul Qur’an Wa Rasmul Qur’an - Ondeng, Syarifuddin; Shahib, Muhamamd Amin; A, Asrullah (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Jam'u Al-Qur'an wa Rosmuhu/Kitabatuhu are two words that are identical in meaning, that is, apart from being interpreted as memorizing, they also mean writing. As with preserving the Koran, these two techniques have been used since the time of the Prophet PBUH, Abu Bakr and Uthman. It's just that in the early period the method of memorization was prioritized, while in the last period the priority was on the method of writing, in order to reduce differences in Qira'ah. The Al-Qur'an during the time of the Prophet SAW was collected by rote and memory, as well as notes that are still scattered around. During Abu Bakr's time, apart from being collected in memorized form, notes were also collected, giving birth to separate Suhuf. During Uthman's time, all the separate memorizations and Suhuf were combined into one, so it was called the Imam's Mushaf. The next period of preservation of the Al-Qur'an was marked by the addition of dots and harakat as well as the refinement of written words in the Ottoman Rasm, as well as the printing of the Al-Qur'an in various countries.